2014
DOI: 10.1016/j.scico.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for modelling usability in a holistic MDD method

Abstract: Abstract. Holistic methods for Model-Driven Development (MDD) aim to model all the system features in a conceptual model. This conceptual model is the input for a model compiler that can generate software systems by means of automatic transformations. However, in general, MDD methods focus on modelling the structure and functionality of systems, relegating the interaction and usability features to manual implementations at the last steps of the software development process. Some usability features are strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The proposal is based on model-to-model and model-to-code transformations. As proof of concept, they had applied their proposal to an existing MDD method called the OO-method and they have measured its efficiency [16]. In another work, STATUS patterns have been chosen because the authors solve usability issues at conceptual level.…”
Section: Related Workmentioning
confidence: 99%
“…The proposal is based on model-to-model and model-to-code transformations. As proof of concept, they had applied their proposal to an existing MDD method called the OO-method and they have measured its efficiency [16]. In another work, STATUS patterns have been chosen because the authors solve usability issues at conceptual level.…”
Section: Related Workmentioning
confidence: 99%
“…In Panach et al [16], the authors have addressed the usability features related to the system functionality, which may involve important changes in the system architecture (Functional Usability Features FUFs). The FUFs are abstractly represented by conceptual primitives that will extend the conceptual model of an existing model-driven development (MDD) method.…”
Section: Related Workmentioning
confidence: 99%
“…Actually, at this stage, since it is costly to go back and make major changes to the design, it has been suggested that usability should be conducted at the early stage of the development process [17]. Within this context, the challenge of evaluating the usability in a model-driven development process has been the aim of several research works [16] [3] [7] [1]. The majority of these works aim to control the model transformation process according to a set of usability attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Another difficulty in the context of customization through transformation rules is that it typically requires skills in a specific transformation language (e.g., ATL or QVT) [2,9]. This motivated a recent approach for supporting usability experts through a dedicated Domain Specific Transformation Language (DSTL) [22].…”
Section: Related Workmentioning
confidence: 99%